Metabolic changes in vestibular and visual cortices in acute vestibular neuritis - Bense, S; Bartenstein, Peter; Lochmann, Matthias; Schlindwein, P; Brandt, T; Dieterich, Marianne (Annals of Neurology, 2004)
Five right-handed patients with a right-sided vestibular neuritis were examined twice with fluorodeoxyglucose positron emission tomography while lying supine with eyes closed: once during the acute stage (mean, 6.6 days) and then 3 months later when central vestibular compensation had occurred. Regional cerebral glucose metabolism (rCGM) was significantly increased (p < 0.001 uncorrected) during the acute stage in multisensory vestibular cortical and subcortical areas (parietoinsular vestibular cortex in the posterior insula, posterolateral thalamus, anterior cingulate gyrus [Brodmann area 32/24], pontomesencephalic brainstem, hippocampus). Simultaneously, there was a significant rCGM decrease in the visual (Brodmann area 17 to 19) and somatosensory cortex areas in the postcentral gyrus as well as in parts of the auditory cortex (transverse temporal gyrus). Fluorodeoxyglucose positron emission tomography thus allows imaging of the cortical activation pattern that is induced by unilateral peripheral vestibular loss. It was possible to demonstrate that the central vestibular system including the vestibular cortex exhibits a visual-vestibular activation-deactivation pattern during the acute stage of vestibular neuritis similar to that in healthy volunteers during unilateral labyrinthine stimulation. Contrary to experimental vestibular stimulation, the activation of the vestibular cortex was not bilateral but was unilateral and contralateral to the right-sided labyrinthine failure.
UnivIS-Import:2015-03-09:Pub.2004.phil.dps.iss.pspbio.metabo_4
Keywords: Metabolic changes; cortices; vestibular; visual; neuritis